Intermittent Supplementation with Far-Red Light Accelerates Leaf and Bud Development and Increases Yield in Lettuce - Yanke Liu; Rong Ye; Xinying Gao; Rongcheng Lin; Yang Li (Plants)
Supplementation with far-red light in controlled environment agriculture production can enhance yield by triggering the shade avoidance syndrome. However, the effectiveness of this yield enhancement can be further improved through intermittent far-red light supplementation. In this study, the effects are explored of varying far-red light photon intensities and intermittent exposure durations—specifically at 5, 15, 30, and 45 min intervals—on the growth and development of lettuce (Lactuca sativa) in plant factories, while maintaining a constant red light photon flux and daily light integral. The results showed that compared to constant far-red light, 30 min intermittent far-red light increased yield by 11.7% and the number of leaves and buds by 2.66. Furthermore, the various metrics demonstrated that intermittent far-red light supplementation enhanced the overall effectiveness of the far-red light treatment. This was validated by analyzing phytohormone content and the expression of genes related to hormone metabolism and transport at the tip of the lettuce stems. Transcriptome analysis revealed that the differences in gene expression between treatments were primarily concentrated in genes related to signaling, hormone metabolism, and transport. Weighted Gene Co-expression Network Analysis identified the co-expression modules associated with yield and quality. Additionally, dynamic expression analysis showed genes involved to far-red photoreception, response, and hormone metabolism and transport exhibited optimal rhythmic responses only under 30 min intermittent far-red light supplementation. This suggests that intermittent far-red light irradiation at 30 min intervals is the most effective for activating far-red light signaling influencing hormone metabolism and transport, thereby accelerating the growth of lettuce leaves and buds and ultimately increasing yield.